THE WAYS OF OVERCOMING DIFFICULTIES IN TEACHING PUPILS PHRASAL VERBS IN ENGLISH - Usmonova Ruxsora Ilyos Qizi (Galaxy International Interdisciplinary Research Journal, 2021)
It’s difficult to teach phrasal verbs. Many studies have demonstrated that contextualization has a significant favorable impact on students’ ability to understand the correct meaning of a phrasal word. In this article, you’ll learn about some effective ways to deliver phrasal verbs in context to help students grasp them better. This page also includes some additional teaching suggestions for phrasal verbs.This article includes that characteristics of phrasal verbs, types, functional approach of teaching them in English, some techniques, resources of eliminating difficulties.